Fracturing the penal state: State actors and the role of conflict in penal change - Rubin, Ashley T. (Theoretical criminology, 2017)
The concept of a penal or carceral state has quickly become a staple in punishment and criminal justice literatures. However, the concept, which suffers from a proliferation of meanings and is frequently undefined, gives readers the impression that there is a single, unified, and actor-less state responsible for punishment. This contradicts the thrust of recent punishment literature, which emphasizes fragmentation, variegation, and constant conflict across the actors and institutions that shape penal policy and practice. Using a case study of late-century Michigan, this article develops an analytical approach that fractures the penal state. We demonstrate that the penal state represents a messy, often conflicted amalgamation of the various branches and actors in charge of punishment, who resist the aims and policies sought by their fellow state actors. Ultimately, we argue that fracture is itself a variable that scholars must measure empirically and incorporate into their accounts of penal change.